2020
DOI: 10.1029/2020ja027772
|View full text |Cite
|
Sign up to set email alerts
|

Statistical Dependence of EMIC Wave Scattering on Wave and Plasma Parameters

Abstract: A recent statistical study (Qin et al., 2018, https://doi.org/10.1029/2018JA025419) has suggested that not all electromagnetic ion cyclotron (EMIC) waves can scatter relativistic electrons. However, knowledge of the factors that influence the EMIC wave scattering efficiency is still limited in observations. In our study, we perform 6 years of analysis of data from 2013 to 2018, with relativistic electron precipitation (REP) observed by POES and EMIC wave observations from Van Allen Probes. The coincidence occu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 70 publications
1
19
0
1
Order By: Relevance
“…Lee et al, 2013), suggesting that if POES is indeed less than ∼0.2 in L away from RBSP-A, the same EMIC waves should likely also be present at the L-shell of POES but not so often at larger distances-Although the actual EMIC wave region size can reach up to ∼2-3R E (Blum et al, 2017). We further require |Δt| < 20 min (UT) as in M. Qin et al (2020), because even if many EMIC waves can persist for 1 h or longer, we cannot predict when they actually end. A condition of |ΔMLT| < 20 min is also imposed because Blum et al (2017) suggest that many EMIC wave events cover at least 20 min in MLT.…”
Section: Event Selection Methodsmentioning
confidence: 97%
See 2 more Smart Citations
“…Lee et al, 2013), suggesting that if POES is indeed less than ∼0.2 in L away from RBSP-A, the same EMIC waves should likely also be present at the L-shell of POES but not so often at larger distances-Although the actual EMIC wave region size can reach up to ∼2-3R E (Blum et al, 2017). We further require |Δt| < 20 min (UT) as in M. Qin et al (2020), because even if many EMIC waves can persist for 1 h or longer, we cannot predict when they actually end. A condition of |ΔMLT| < 20 min is also imposed because Blum et al (2017) suggest that many EMIC wave events cover at least 20 min in MLT.…”
Section: Event Selection Methodsmentioning
confidence: 97%
“…Qin et al, 2019;Sandanger et al, 2007). However, recent statistical studies of EMIC waves (observed by the Van Allen probes) and conjugate REP measured by low-earth-orbit Polar Environmental Satellites (POES) suggest that only ∼20% of the observed EMIC waves may be associated with >0.7 MeV electron precipitation, with a complex dependence on wave and plasma parameters (M. Qin et al, 2018Qin et al, , 2020. Based on the cold plasma theory, the minimum electron energy for cyclotron resonance with EMIC waves should be lower for a higher electron plasma to gyrofrequency ratio F pe /F ce or for a higher upper cutoff frequency F UC of EMIC waves (Summers & Thorne, 2003).…”
Section: Research Articlementioning
confidence: 99%
See 1 more Smart Citation
“…One of the important aspects of EMIC waves is their important role in pitch‐angle scattering relativistic electrons in the outer radiation belt via cyclotron resonant interactions, thus leading to the precipitation of both tens of kilo‐electronvolts ions and million electronvolts electrons to the ionosphere (e.g., Albert & Bortnik, 2009; Denton et al., 2019; Engebretson et al., 2015; Jordanova et al., 2008; Khazanov & Gamayunov, 2007; L. Blum et al., 2019; L. W. Blum et al., 2020; Lee et al., 2020; Lessard et al., 2019; Loto’aniu et al., 2006; Meredith et al., 2003; Miyoshi et al., 2008; Qin et al., 2018; Qin et al., 2020; Thorne, 2010; Ukhorskiy et al., 2010; Usanova et al., 2014; Z. Li et al., 2014). The radiation belt electron dropout in association with EMIC waves has been shown as decreases in phase space density (PSD) (e.g., Engebretson et al., 2015, 2018; Shprits et al., 2016; Turner et al., 2014; Xiang et al., 2017; Zhang et al., 2016).…”
Section: Introductionmentioning
confidence: 99%
“…EMIC waves, which are known to effectively scatter relativistic electrons (Li et al., 2013; Qin et al., 2018, 2019, 2020; Summers & Thorne, 2003) as well as ∼100s keV electrons (Capannolo, Li, Ma, Chen, et al., 2019; Capannolo, Li, Ma, Shen, et al., 2019; Chen et al., 2016; Clilverd et al., 2015; Hendry et al., 2017), were not detected within the conjunction region (Figure 1d), and thus were unlikely to play a role in this precipitation event. It is also suggested that Ultra‐Low‐Frequency (ULF) waves could play a potential role in precipitating energetic electrons, either by modulating the whistler‐mode wave intensity (Breneman et al., 2015, 2020; Halford et al., 2015; Jaynes et al., 2015) or transporting particles radially inward where the loss cone becomes larger (Brito et al., 2012, 2015).…”
Section: Observationsmentioning
confidence: 99%